Non-Functional Requirements Tendering Based on Knowledge Management: the Merlinn Framework (2018)
Requirements solicitation is considered the basis for the next stages of software development, and involves, among others, collecting and analyzing functional and non-functional requirements (FNR). The literature shows that: (i) there is a lack of NFR elicitation mechanisms and (ii) there is a lack of awareness of NFR by stakeholders. In this sense, this article presents the framework for the tendering of non-functional requirements based on knowledge management (called Merlinn) that seeks the visualization of NFRs and the active participation of stakeholders. Merlinn’s evaluation was conducted through a study case in a software development company. The results of the evaluation show that Merlinn can be ideal and adaptable to support the organization’s NRF tendering process, so that it impacts the quality of the software product.